Phenotypic and Genotypic Characterization of DEPDC5-Related Familial Focal Epilepsy: Case Series and Literature Review - Zhang, Xuan; Huang, Zhaoyang; Liu, Jianghong; Li, Mingyu; Zhao, Xiaoling; Ye, Jing; Wang, Yuping (Frontiers in Neurology, 2021)
Mutations in the disheveled, Egl-10 and domain-containing protein 5 (DEPDC5) recently have been identified as a common cause of focal epilepsy syndromes. The association between phenotype and genotype of DEPDC5 mutation has not been adequately characterized. We studied four families with familial focal epilepsy carrying DEPDC5 mutations. Four novel DEPDC5 mutations were identified by next-generation sequencing, including two missense mutations (c.1729 >A, c.3260G>A), one splicing mutation (c.280-1G>A) and one frameshift mutation (c.515_516delinsT). We found that patients carrying different DEPDC5 mutation have different clinical manifestations. Incomplete penetrance is a prominent feature of DEPDC5-related epilepsy, with the rate of penetrance ranging from 25% to 100%. About 21.4% of patients with DEPDC5-related familial focal epilepsy are refractory to treatments. We further reviewed the correlation of genotype and phenotype in all previous literature regarding DEPDC5-related epilepsy. Our study suggested that the type of DEPDC5 mutation might provide important information for the prognosis evaluation.